Women irrigators and leaders in the West Gandak Scheme, Nepal - van Koppen, Barbara; Etten, Jacob van; Bajracharya, P.; Tuladhar, A. (International Water Management Institute, 2001)
Examines the gendered organization of irrigated farming and identifies processes of inclusion and exclusion of women irrigators and women leaders in water users committees. The research evaluates the success of efforts by the newly formed Water Users Association to include women. Recommendations based on the findings are made to address the problems faced by the women irrigators and leaders in the West Gandak scheme.